Christian-Muslin co-operation in a secular age. Areas of collaboration - ks. Janusz Balicki (Chrześcijaństwo-Świat-Polityka)
In recent years, the Muslim population in Europe has increased in a significant way due to the large inflow of immigrants from Muslim countries caused by the war in Syria and the activity of the Islamic State. In the long history of Christian-Muslim relations, these two religions, with their respective political powers, were involved in many conflicts. Europe has become very secular and lost some of her Christian values. It would be interesting to see if the influx of Muslims with strong religious values creates an opportunity for Christians to co-operate in some areas and to strengthen common beliefs. The aim of this article is to identify possible areas of co-operation between Christians and Muslims in the secular Europe and the basic conditions that must be met to make this co-operation possible. The answer is given through the analysis of the following issues: main disputes between Christian churches and liberal legislation regarding marriage, family values and the protection of human life; analysis of the world wide Muslim beliefs and attitude to family and protection of life; analysis of the co-operation of Christians and Muslims at the UN, in different States or NGOs in the area of legislation protection as well as the co-operation of Christians and Muslims in Great Britain at the basic level. At the end of the article, the main results and conclusions are presented.